Karakteristik Stomata dan Trikoma Daun Kirinyuh (Chromolaena odorata L.) - Salamah, Hatipah; Oktavia, Siti Dela; Nuraini, Savira; Muliyah, Evi (Mahesa Research Center, 2024)
Kirinyuh (Chromolaena odorata L.) is a shrub that belongs to the Asteraceae family and is classified as a dicotyledonous plant. Each plant has characteristics that are generally different, such as stomata and trichomes owned by kirinyuh leaves. This study aims to analyze the characteristics of stomata and trichomes of kirinyuh leaves, examine the structure of kirinyuh leaf layers based on transverse sections, and calculate the density of stomata and trichomes in paradermal sections of kirinyuh leaves. This study used a laboratory experimental method by making simple microscopic section preparations. This study was conducted at the Laboratory of the Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, Jakarta. Samples were obtained from Ciomas Permai Housing, Ciapus Village, Ciomas District, Bogor Regency. The results of this study show that paradermal sections on the adaxial cross-section, kirinyuh leaves have irregular epidermis with anomocytic oval type stomata with kidney-like guard cells and non-glandular type trichomes with multicellular uniseriate type. The stomata found were 115 with a density of 8.38 stomata/mm2 and an index of 0.056 mm2, while the trichomes found were 3 with a density of 0.21 trichomes/mm2. In the transverse section, the layers of kirinyuh leaves are composed of upper epidermis tissue, palisade tissue, blood vessel bundles, sponges, lower epidermis, and trichomes.